Aporte al desarrollo de un soporte tridimensional de gelatina- alcohol polivinílico para el estudio de tumores sólidos de mama. Fase II: Optimización de propiedades mecánicas, reológicas, microestructurales y de reactividad biológica in vitro (2023)
Breast cancer is the most common type of cancer worldwide, affecting about 2,261,419 women in 2020 with an incidence rate of 47.8%. Its 5-year survival rate is approximately 90% for non-invasive phases and about 70% for non-metastatic invasive phases. (E, Hernandez et al., 2016) In Colombia, breast cancer is one of the main problems in public health, and addressing this neoplasia is necessary (Gamboa et al., 2016). Current research is focused on pharmacological treatment; however, around 95% of these treatments are not FDA-approved due to a lack of preclinical models that imitate the tumor microenvironment. Tissue engineering has introduced the development of three-dimensional supports using natural or synthetic biomaterials that can mimic the tumor microenvironment, allowing for a more precise evaluation of what occurs in vivo. This second-phase project aims to contribute to the development of a gelatin-polyvinyl alcohol three-dimensional support for the study of solid breast tumors, optimizing mechanical, rheological, microstructural, and in vitro biological reactivity properties. The mixture of these two biomaterials (gelatin-polyvinyl alcohol) allows for obtaining supports with different microstructural and in vitro biological reactivity properties appropriate for the development of a three-dimensional solid breast tumor model. Gelatin is a widely used biomaterial for support development and has excellent cell viability, while polyvinyl alcohol is mostly used for the fabrication of phantom tissues, as its acoustic and mechanical properties can be easily adjusted to mimic those of soft tissues due to its high degree of elasticity (L, Chunyang et al., 2020). Therefore, eight supports were developed with both biopolymers at concentrations of 10mg/g and 14mg/g with PVA 30,000 Da and 180,000 Da in ratios of 5:5, 7:3, and 9:1. From the tests for percentage of porosity, tension, compression, dynamic rheology, and cytotoxicity, it was found that the percentage of porosity was >80%, in the second and third cases the young's modulus was within the range reported in the literature for solid breast tumors (800 Pa-3000 Pa), in the fourth case, it was found that the viscoelastic behavior of the supports is more of a solid than a liquid and has great resistance to deformation. As for cytotoxicity and viability tests, they complied with ISO 10993-5.